2022
DOI: 10.3390/biology11020320
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Biodiversity, Carbon Storage and the Potential for Increasing Negative Feedbacks on Climate Change in Shallow Waters of the Antarctic Peninsula

Abstract: The importance of cold-water blue carbon as biological carbon pumps that sequester carbon into ocean sediments is now being realised. Most polar blue carbon research to date has focussed on deep water, yet the highest productivity is in the shallows. This study measured the functional biodiversity and carbon standing stock accumulated by shallow-water (<25 m) benthic assemblages on both hard and soft substrata on the Antarctic Peninsula (WAP, 67°S). Soft substrata benthic assemblages (391 ± 499 t C km−2) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…However, the challenge remains to find a causal relationship between this aspect of biology and potential environmental drivers. The relationship between environmental variables and the zoobenthic carbon values could be masked by the fact that environmental conditions were only measured at one time point during the year and of course conditions at our sample sites will change through the seasons; however, studies in Antarctica showed no change in zoobenthic blue carbon with seasons (Morley et al, 2022). Environmental variables did not facilitate defining specific habitats from our sample sites; however, a PCA cluster did show an obvious separation of environmental variables between the Norge shelf and trough sites and also showed an expected gradual change across sites, shown by Jørgensen, Ljubin et al (2015) (Figure 3).…”
Section: Discussionmentioning
confidence: 91%
“…However, the challenge remains to find a causal relationship between this aspect of biology and potential environmental drivers. The relationship between environmental variables and the zoobenthic carbon values could be masked by the fact that environmental conditions were only measured at one time point during the year and of course conditions at our sample sites will change through the seasons; however, studies in Antarctica showed no change in zoobenthic blue carbon with seasons (Morley et al, 2022). Environmental variables did not facilitate defining specific habitats from our sample sites; however, a PCA cluster did show an obvious separation of environmental variables between the Norge shelf and trough sites and also showed an expected gradual change across sites, shown by Jørgensen, Ljubin et al (2015) (Figure 3).…”
Section: Discussionmentioning
confidence: 91%
“…Ideally this information can be overlayed with VME and infaunal assemblage mapping, biogeochemistry, and population genetics to estimate blue carbon connectivity from key model sequesters (e.g., corals, sponges and echinoderms). This type of information would validate carbon storage and sequestration estimates based on functional groups at finer temporal and spatial scales (e.g., per population, per area, per year over time) both offshore (e.g., Barnes and Sands, 2017;Barnes et al, 2021) and nearshore (e.g., Morley et al, 2022). However, such estimates also rely on knowledge of a taxon's traits such as feeding strategy, mobility and lifestyle, which is lacking for most benthic taxa (www.SCAR-MarBIN.be).…”
Section: Future Seafloor Blue Carbon Priority Research Areasmentioning
confidence: 83%
“…In this manner, the inclusion of blue carbon research into MSP must also grapple with a contiguous managed area that includes ABNJ fisheries across a vast area extending into the Scotia arc in the sub-Antarctic. Given the diversity of habitats and high endemism to consider (Morley et al, 2022), a precautionary and informed management approach to conservation will be imperative.…”
Section: Forward Lookmentioning
confidence: 99%
“…The large hovering style AUVs; "Autonomous Benthic Explorer" and "Sentry", work in steep terrain and in tandem with manned submersibles [31] . While these large AUVs have proved valuable at collecting biological data on seamounts and mid-Atlantic ridges [32] , they require a dedicated research vessel for their operation and the associated costs are prohibitive to many research projects.…”
Section: Autonomous Underwater Vehiclesmentioning
confidence: 99%